RELEVANSI FAKTA HUKUM DALAM PENGGUNAAN SIFAT MELAWAN HUKUM NEGATIF - Luh Rina Apriani (Komisi Yudisial RI, 2011)
ABSTRACTThis paper examines the relevance of the term 'nature against the law in negative sense' as the reason for the suppression of criminal law to the facts revealed at trial. The relevance is important because proving the existence of nature against the law in a negative sense associated with the values of decency and living habits in society. The judges in this case seems to disregard to assess the facts of existing law as a unity, and value it as something that is partial and stand alone. Logical thinking is also not used when assembling the facts to one another when it is impossible that the defendant's actions are assumed to serve the public interest when the public interest that wants to be served has been completed long before the defendant's caught redhanded transporting timber without legal documentation. When the judges missed in assessing the facts that are based on a reasonable interpretation and logical thought patterns, the decision therein therefore is a decision that denies the values of justice, expediency, and legal certainty as seen in this decision.Keywords: nature against the law in negative sense, relevance, legal facts ABSTRAKTulisan ini menguji relevansi definisi